Republic of Estonia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper and Statistical Appendix examines the developments in the intergovernmental fiscal relations for the Republic of Estonia. The paper highlights that intergovernmental relations in Estonia have been marked in recent years by a strong push in the direction of fiscal decentralization. This trend has been part of the broader process of structural change, including privatization and liberalization of markets in Estonia. The paper analyzes the evolution of the financial sector. It also examines European Union accession and the economic policy of Estonia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet